Resubmission of VO#027 wall type - single & double sided brick wall [100 mm thick] - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the resubmission of type of brick wall that includes detail of single & double sided wall of BRACU new campus project.